Radiofrequency ablation of genicular nerves prior to total knee replacement has no effect on postoperative pain outcomes: a prospective randomized sham-controlled trial with 6-month follow-up. Issue 6 (25th April 2019) - Walega, David; McCormick, Zachary; Manning, David; Avram, Michael
Abstract : Background and objectives: Refractory chronic knee pain from osteoarthritis (OA) is commonly treated with total knee arthroplasty (TKA). TKA can be associated with severe postoperative pain and persistent postsurgical knee pain. Poorly controlled postoperative pain can negatively effect functional outcomes following TKA, and effective opioid-sparing analgesia is key to the ideal recovery. Genicular nerve radiofrequency ablation (GN-RFA) has been shown in several trials to be clinically effective in patients with severe refractory knee pain from OA. We aimed to assess if preoperative GN-RFA would improve postoperative pain outcomes following TKA. Methods: This was a sham-control prospective clinical trial in which blinded participants were randomized to image-guided GN-RFA or a simulated sham procedure 2-6 weeks prior to elective TKA. Outcomes were assessed at 48 hours and 1, 3 and 6 months following TKA. Results: Seventy participants enrolled in this study. As compared with sham controls, GN-RFA had no treatment effect on postoperative opioid consumption, pain or functional measures at any time point. Conclusions: Cooled RFA of the superior lateral, superior medial and inferomedial genicular nerves, when performed 2–6 weeks prior to elective TKA as part of a multimodal postoperative pain management regime, had no measurable effect on postoperative opioid use, analgesia use or function in the 48 hours following surgery. In addition, we found no longer term effect on outcome measures 1, 3 and 6 months after TKA. Trial registration number: NCT02746874 .